ARTIFICIAL INCUBATION OF THE HORNED GUAN OREOPHASIS DERBIANUS (AVES: CRACIDAE) EGGS - González-García, Fernando; Porras, Catalina; Vargas, Juan Julián (Instituto de Ecología, A.C., 2006)
Artificial incubation is a favorable technique for reproduction programs of threatened or endangered species. However, implementing a method for monitoring the incubation process is highly important. Temperature and humidity are key physical parameters for egg incubation leading to successful hatching. We used artificial incubation as an alternative to natural incubation of the Horned Guan Oreophasis derbianus. Weight and density loss were used to monitor the incubation process of the eggs, considering a final weight and density loss of 15%. Before incubation, the eggs weighed an average of 161.04 ± 9.87 g (n = 24) and measured 85.57 ± 3.16 mm x 57.52 ± 1.31 mm (n = 15). Density and volume averages of eggs were 1.08 ± 0.036 g-cm3 (n = 15) and 142.40 ± 10.46 g-cm3 (n = 15), respectively. Of 24 eggs, 15 (62.5 %) were fertile, and seven resulted in successful hatching (46.6 % hatch). The pip to hatch time in two eggs was 14 y 19 hours, respectively. The eggs were incubated at a temperature of 37.5°C (dry bulb) and a relative humidity of 53-56% (28.8-30.1°C) (wet bulb) throughout the 33-35 day incubation period. In eight cases, the embryos reached full development but failed to hatch successfully, likely due to improper humidity levels. This is the first published record of Horned Guan artificial incubation parameters and its monitoring process.